Ordinances of the Town of North Kingstown 6 (1896) - (:unkn) unknown (My University, 1896)
An Ordinance Establishing the Ordinances of the Town of North Kingstown, and Prescribing the Time When They Shall Go into Effect, Ch. 6: Every person who shall play at ball, or any other game or sport, throw stones or other missiles, discharge any gun, pistol, or other fire-arms, fire any torpedo, fire-cracker, or other noisy missile in any public place, street, or highway in this town, shall, on conviction thereof, pay a fine of not less than one dollar, nor more than five dollars, for every such offense.
Keywords: DISCHARGE